Outpost / 2. - Aguirre, Ann (Razorland, 2012)
Deuce struggles for respect in a new topside town where she is treated like a child and avoided by Fade, a situation that compels her to volunteer for patrol duty and protect topside citizens from an unexpected upsurge in Freak activity.